Performance of compulsive behavior in rats is not a unitary phenomenon – validation of separate functional components in compulsive checking behavior. (16th June 2014) - Tucci, Mark C.; Dvorkin‐Gheva, Anna; Johnson, Eric; Cheon, Paul; Taji, Leena; Agarwal, Arnav; Foster, Jane; Szechtman, Henry
Abstract A previous analysis of the quinpirole sensitisation rat model of obsessive‐compulsive disorder revealed that the behavioral phenotype of compulsive checking consists of three constitutive components – vigor of checking performance, focus on the task of checking, and satiety following a bout of checking. As confirmation of this analysis, the aim of the present study was to reconstitute, without quinpirole treatment, each of the putative components, with the expectation that these would self‐assemble into compulsive checking. To reconstitute vigor and satiety, the employed treatment was a bilateral lesion of the nucleus accumbens core (NAc), as this treatment was shown previously to exaggerate these components. To reconstitute focus, the employed treatment was a low dose of the serotonin‐1A receptor agonist 8‐hydroxy‐2‐(di‐n‐propylamino) tetralin hydrochloride (DPAT) (0.0625 mg/kg), as high doses of this drug induce compulsive behavior and exacerbate focus. Results showed that injection of DPAT to NAc lesion rats did yield compulsive checking. Neither the drug alone nor the NAc lesion by itself produced compulsive checking. The demonstrated synthesis of compulsive checking by the combined treatment of low‐dose DPAT and NAc lesion strengthened the previous fractionation of the model obsessive‐compulsive disorder phenotype into three constitutive components, and suggested a role for serotonin‐1A receptors outside the NAc in enhanced focus on the task of checking.